Morfología vegetal neotropical - Pérez-García, Blanca (2002)
An analysis on plant morphology and the sources that are important to the morphologic interpretations is done. An additional analysis is presented on all published papers in this subject by the Revista de Biología Tropical since its foundation, as well as its contribution to the plant morphology development in the neotropics.